Akselerasi Desa Open Defecation Free melalui PAR dan CLTS di Bantaran Sungai Desa Berembang - Fiqi Nurmanda Sari; Nurfadliyati Nurfadliyati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Open defecation in riverbank areas is a sanitation challenge that involves cultural normalization and infrastructure limitations. This community service project aims to transform the sanitation behavior of the people of Berembang Village, Muaro Jambi District. The service method used Participatory Action Research (PAR) integrated with Community-Led Total Sanitation (CLTS). The intervention procedure consisted of three stages: (1) social triggering to build awareness, (2) policy advocacy for the formulation of village regulations, and (3) provision of infrastructure incentives for low-income communities. The results of the community service showed a shift in community perception towards health awareness, as evidenced by the formation of an anti-BABS “Social Contract.” Institutionally, this community service successfully initiated a draft Village Regulation as an instrument of social control and ensured the sustainability of the program. Physically, the toilet stimulus assistance, which was built independently, improved access to more adequate sanitation. The integration of cultural, structural, and institutional aspects was effective in accelerating the achievement of Open Defecation Free (ODF) status in the riverbank area, particularly in Berembang Village.